Immune cell profiling of the ICAM1 p.K56M heart failure with preserved ejection fraction risk variant - Jing Gao; Pedro Giro; Joseph A. Delaney; Laura Rasmussen‐Torvik; Kent D. Taylor; Edward B. Thorp; Margaret F. Doyle; Matthew J. Feinstein; Colleen M. Sitlani; Nels Olson; Russell Tracy; Sanjiv J. Shah; et al. (ESC Heart Failure)
Abstract Aims Intercellular adhesion molecule‐1 (ICAM‐1) facilitates inflammation via leucocyte recruitment and has been implicated in heart failure with preserved ejection fraction (HFpEF). Approximately 35% of African American individuals carry a copy of an ICAM1 missense variant (rs5491; p.K56M), which is associated with an increased risk of HFpEF. The pathways by which rs5491 increases HFpEF risk are not well defined. We evaluated the circulating immune cell profile of rs5491. Methods Among African American individuals in the Multi‐Ethnic Study of Atherosclerosis, we evaluated the associations of rs5491 with 29 circulating peripheral blood mononuclear cell subsets. The top immune cells were then related to echocardiographic measures of structure and function. Results Among 502 individuals with immune cell profiling (mean age 63 years, 51% female), 191 individuals (38%) had at least one copy of rs5491. Each additional rs5491 allele was significantly associated with higher proportions of Tc17 CD8+ cytotoxic T cells (β = 1.34, SE = 0.45, P = 9.5 × 10−5) and Tc2 CD8+ cytotoxic T cells (β = 1.19, SE = 0.44, P = 0.00012). There were no other associations noted between rs5491 and the remaining immune cells. A higher proportion of Tc17 cells was significantly associated with a higher left ventricular ejection fraction, E/e′ average and right ventricular systolic pressure (RVSP), while a higher proportion of Tc2 cells was significantly associated with a higher RVSP. Conclusions The ICAM1 p.K56M variant (rs5491) carries a distinct and inflammatory T‐cell subset profile. These cytotoxic T cells are in turn associated with alterations in cardiac function and adverse haemodynamics later in life, thus providing insight into pathways by which rs5491 may increase the risk of HFpEF.